Frailty in cardiovascular disease: Screening tools - Zão, Ana (2019)
Cardiovascular disease (CVD) is the leading cause of death in developed countries and disproportionately affects older adults. Frailty is a complex clinical syndrome with multiple causes and contributing factors in which there is increased vulnerability when exposed to a minor stressor and increased risk for adverse outcomes, such as disability, hospitalization and mortality. Frailty is an important prognostic factor in patients with CVD, and so identifying this feature when assessing these patients may help to individually tailor cardiovascular treatment. The first step is to identify frailty. Several tools have been validated as screening methods for frailty. However, they diverge with regard to complexity, nature, feasibility and the outcome they can predict. The aim of this review is to describe the available screening tools for frailty and to examine their usefulness in patients with CVD.